Pemberdayaan Petani Lokal Melalui Pelatihan Pembuatan Pupuk Organik Berbasis Kotoran Ayam dan Biochar di Desa Pematang Guntung - Misdawati, Misdawati; Mayly, Syarifa; Dibisono, M. Yusuf (Unri Conference Series: Community Engagement, 2024)
This service activity was carried out in Lestari Dadi Village with target partners namely members of Sri Muliya Farmers Group. This activity aims to increase the community's knowledge and skills about environmentally friendly agriculture, bioconversion of organic fertilizer from cow manure with maggot larvae. The main problem for farmers is that environmentally friendly agriculture has not been implemented by utilizing bioconversion of cow dung waste with maggot larvae. Implementation methods are Pretest, Counseling and training on maggot cultivation, training on bioconversion of cow dung waste with maggot larvae into organic fertilizer, Post test. The results of this Community Service show that there is an increase and training in farmers' knowledge and skills in converting cow manure with maggot larvae.